Time to build and the real-options channel of residential investment - Oh, Hyunseung; Yoon, Chamna (Journal of Financial Economics, 2020)
A standard real-options model predicts that time-to-build investment could be delayed by uncertainty over future revenue. We quantify the first-order importance of this mechanism in the 2002–2011 housing boom-bust cycle by developing and estimating a model of sequential irreversible investment with stochastic bottlenecks. We find that the main driver of construction delays during the boom is construction bottlenecks. However, further delay in construction during the bust is caused by an increase in uncertainty, which grew by 21.6% between 2002 and 2009. The model can account for more than one-third of the decline in residential investment between 2002 and 2009.